EFFECT OF ESSENTIAL OIL EXTRACT FROM LEMONGRASS (Cymbopogon citratus) LEAVES ON VAIABILITY OF SOME PATHOGENIC BACTERIA AND SENSORY PROPERTIES OF FISH BALLS - Kamona, Zaid K.; Alzobaay, Amer H. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Lemongrass (Cymbopogon citratus) plant belongs to the Gramineae family. Lemongrass leaves essential oils were extracted by Clevenger method, antibacterial, MIC and MBC were evaluated against some gram positive and gram negative bacteria. Bacillus cereus, Staphylococcus aureus, and micrococcus spp., recorded high sensitivity to essential oil with inhibition zone reached (40, 32, and 28) mm respectively. While Pseudomonas spp., Salmonella typhimurium, and Escherichia coli recorded (20, 20, and 22) mm respectively. MIC and MBC values reached (3, 6.5) % respectively for gram-positive bacteria and (25,50) % respectively for gram-negative bacteria. C.citratus leaves essential oil showed superior efficiency in reduction count of total microorganisms, coliform bacteria, psychrotrophic bacteria, Staphylococcus aureus, and molds and yeasts, as well as the elongated shelf life for 15 days of fish balls treated with (5,10) µl\gram of essential oil under refrigerated storage compared with control treatment ( no oil added) which excluded for test after 6 days of refrigerated storage because microbial load and bad quality. Fish balls samples Lg10 (treated with 10µl\g of essential oil) gained best sensorial properties of color, texture, flavor, taste and overall acceptability were recorded 9/9 at the end of storage compared with treatment Lg5 (5µl\g essential oil added)  which gained acceptable sensorial score through refrigerated storage periods.